The Cross of Christ in African American Christian Religious Experience: Piety, Politics, and Protest - Williams, Demetrius K. (Lexington Books, 2023)
In The Cross of Christ in African American Christian Religious Experience: Piety, Politics, and Protest, Demetrius K. Williams examines and explores the ideational importance and rhetorical function of cross language and terminology in Black religious experience through an ideological lens. Williams argues that for the first time in Christian history, the European nation of Portugal under the guidance of Prince Henry used the theology of the cross to justify and sustain an exclusive trade of Sub-Saharan African peoples. Claiming that Jesus died on the cross only “to save lost souls” provided a convincing rational for Henry’s exploratory voyages of discovery to West African to exclusively enslave Black bodies. With the confirmation of Catholic Popes and the competition of other European nations, this same rationale would inspire empire building, colonization, and slave-trading, justified on their newly constructed ideological narrative of compassionate evangelism “to save lost souls”. Over time, with massive conversions to the faith of their enslavers, Black people’s Christian religious experiences would articulate a response to the world that held them in thralldom. That response would be articulated most consistently and effectively through their understanding of the cross of Christ. Williams affirms Howard Thurman’s claim that by “some amazing but vastly creative spiritual insight the slave undertook the redemption of a religion that the master had profaned in his midst.”